A review on customized food fabrication process using Food Layered Manufacturing. (1st May 2022) - Soni, Rahul; Ponappa, K.; Tandon, Puneet
Abstract: 3D printing, an additive manufacturing technique, is being used in many sectors and when it is adopted for the rapid and customized production of food items, the technology is known as food-layered manufacturing (FLM). FLM can be used to prepare customized and texture modified food products, having desired nutritional value and food quality, from different ingredients and additives. This paper reviews the development of various food printing technologies from the perspective of theoretical models to the available commercialized printers. The technologies and their mechanisms, that are used in food 3D printing were studied in detail. Numerous material supplies and recipes had been studied followed by developing an understanding of the role of different food constituents and additives. Food additive manufacturing technology (FLM) was developed by combining digital gastronomy with additive manufacturing technology. Since the technology is at a nascent stage, FLM has many challenges and limitations such as limited shelf-life, food safety, etc. FLM provides opportunities, like nutritious food, reduction in food wastage, automated cooking, etc. The study aims to find a way to develop a new setup for making personalized, tailor-designed, and nutritious foods because the need for such food items is strongly realized in the present times of the global pandemic. To eliminate the problem of shortage of food, which is caused due to population blast and limitation of the resources, it is high time to adopt the alternate resources as an ingredient to prepare the nutritious foods by using the FLM. Highlights: Personalized foods for people suffering from swallowing or mastication problems. Food customization. Personalized and nutritious foods in the present times of the global pandemic. Temperature is the most important parameter for food printing. Food waste reduction.